PERSEPSI WAJIB PAJAK ORANG PRIBADI PADA TINGKAT KEPATUHAN ATAS PELAKSANAAN SELF ASSESSMENT SYSTEM DAN PENGARUHNYA TERHADAP TINDAKAN PENYELUNDUPAN PAJAK (TAX EVASION): STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA SLEMAN YOGYAKARTA - Indah Puspitasari; Dewi Kusuma Wardani (Jurnal Akuntansi, 2013)
This study aimes to determine whether the perception of individual taxpayer compliance level for the implementation of self-assessment system tax evasion. The research was conducted by distributing questionnaires to individual taxpayers who are in the Kantor Pelayanan Pajak Pratama Sleman Yogyakarta (Tax Office Primary Sleman Yogyakarta). This research is a quantitative study. Sampling method is convinience sampling. Is sampling that is the distributed 70 quesionare, three of the respondents did not fill and 2 did not full completed. So, obtained data from 65 respondents. We used linear regression analysis with SPSS for Windows 17.00. We found that the perception of individual taxpayer compliance level for the implementation of self-assessment system negatively affect (tax evasion). The coesionare correlation coefficient is -0.547. It indicates that there is a moderate or fairly between individual taxpayer perception on the level of compliance on the implementation of selfassessment system for tax evasion. Negative direction indicates that the higher the perception of individual taxpayer compliance level for the implementation of self-assessment system, the lower tax evasion, or vise versa. Keywords: Perception of taxpayer compliance level for the implementation of selfassessment system, tax evasion.